Development of an inhibitive enzyme assay for heavy metal detection using molybdenum-reducing enzyme from Staphylococcus sp. isolate liz1 - Abu Bakar, Nurlizah (2010)
Molybdenum-reducing bacteria were isolated from soil and water samples throughout Malaysia and one isolate from workshop area in Seri Kembangan, Selangor was identified to reduce molybdenum to molybdenum blue in less than 48 hours with the most intense blue-colour colony formation. Further analysis using biochemical test, 16S rRNA ribosomal gene sequence comparison and molecular phylogenetics analysis showed that isolate Point 1 is Gram-positive coccus and grouped under genus Staphylococcus and was submitted to Genbank under accession number of EU828636 as Staphylococcus sp. isolate liz1. The characterization studies showed that the bacterium gave the highest Mo-reducing activity under the combination of 1% glucose, 50 mM molybdate, 5 mM phosphate, at pH 6.0 and temperature 37°C in 48 hours of incubation time. Partial purification and characterization were conducted on crude Mo-reducing enzyme with two anion exchange chromatography columns (Q-Sepharose and Mono Q). Three bands were obtained on the Mono-Q fraction at 25, 40 and 55 kDa using reducing SDS polyacrylamide-gel electrophoresis (SDS-PAGE). Characterization of Mo-reducing enzyme kinetics gave the Km and Vmax values of 5.722 mM and 127.1 nmole Mo-blue/min/mg protein for laboratory-prepared phosphomolybdate (LPPM), and 15.58 mM and 152.8 nmole Mo-blue/min/mg protein for NADH, respectively. The optimum pH and temperature for enzyme were pH 5.0 and 37°C, respectively. The inhibition profiles of heavy metal on Mo-reducing activity were determined and IC50 values were calculated. The results showed that the enzyme has high sensitivity towards copper (0.2845 mg L-1), silver (0.2773 mg L-1), and mercury (0.4187 mg L-1). Three commercialized herbs samples were tested using the developed enzyme assay and the results were compared with that of atomic absorption spectroscopy (AAS) analysis. The results showed that one of the herb sample contained high level of mercury and copper when analysed using AAS (1.016 mg L-1 and 0.421 mg L-1, respectively). The findings were similar to the biological assay system developed for the detection of selected heavy metals, indicating the usefulness of the assay.